Streptococcus Mutans Photoinactivation by Combination of Short Exposure of a Broad-Spectrum Visible Light and Low Concentrations of Photosensitizers - Paschoal, Marco Aurelio [UNESP]; Santos-Pinto, Lourdes [UNESP]; Lin, Meng; Duarte, Simone (Mary Ann Liebert, Inc., 2014)
Objective: Investigate the photodynamic antimicrobial effect by the combination of a novel noncoherent broad spectrum visible light and low concentrations of curcumin and toluidine blue over suspensions of Streptococcus mutans. Background data: Long illumination times to activate photosensitizers (PS) and the use of high concentrations of these drugs in photodynamic antimicrobial chemotherapy (PACT) are limitations of its application as an antimicrobial technology in dental practice. Materials and methods: Planktonic suspensions of S. mutans were standardized and submitted to PACT treatment at low concentrations of curcumin (C) (0.075; 0.75 and 7.5 mu M) and toluidine blue (T) (0.25; 2.5 and 25 mu M) exposed to 42 J/cm(2) (12.2 sec; set power: 3.930 mW) of a white light (WL) (output wavelength range: 400-700 nm; beam diameter: 12 mm) (C+WL+ and T+WL+, PACT groups; incubation time, C: 60 sec; T: 5 min); isolated effect of both C (C+WL-) and T concentrations (T+WL-); effect of light source (C-WL+ and T-WL+) and suspensions neither submitted to PS nor to light-emitting diode (LED) illumination (control groups, C-WL- and T-WL-). Aliquots of each group were diluted and cultured on blood agar plates and the number of colony-forming units (CFU)/mL was recorded, transformed into log(10) and analyzed by ANOVA and Tukey's test at a cutoff value at 0.05. Results: The groups submitted to PACT presented a bacterial reduction value of>5-log(10) to both tested PS in comparison with control groups (p<0.05). PS or light source used alone demonstrated no antimicrobial effect on the number of viable bacterial counts. Conclusions: The combination of a novel noncoherent light at short illumination exposure time with low concentrations of studied PS achieved a lethal photoinactivation of S. mutans, and can be considered an effective antimicrobial in vitro approach for reducing the number of micro-organisms involved with the dental caries process.